The Effect Of Substitution Of Mustard Green Extract As A Natural Colorant In The Manufacture Of Rolled Pancakes - Janusuri, Fisma; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to analyze roll pancakes with green mustard extract substitution as much as 10%, 20%, and 30%. This research was conducted at the culinary arts workshop majoring in family welfare science in October 2021. This type of research was an experimental study using a completely randomized design (CRD) consisting of 3 treatments and 3 repetitions. Data analysis was obtained from Organoleptic Test involving 5 expert panelists. The data obtained were then analyzed using the ANAVA method, if there was a significant effect, it would be continued with the Duncan test. The results showed that the substitution of mustard greens had an effect on the green color of the rolled pancake skin. Which does not affect the shape, aroma, texture and taste. Based on the results of the study, the best quality pancake rolls were in the X3 treatment with a score of 3.60, the best green quality pancake rolls in the X3 treatment with a score of 3.80, the pancake rolls had the best fragrant aroma quality in the X3 treatment with a score 3.13, pancake rolls with the best chewy texture quality in X3 treatment 3.13, roll pancakes with the best porous texture quality in X3 treatment with a score of 3.53, pancake rolls with the best sweet taste quality in X3 treatment with a score of 3.53, very suitable for consumption. So for further research, it is recommended that the use of mustard greens extract should be as much as 30%, namely with X3 treatment.